Strategi Komunikasi Pemangku Kepentingan LSM Rifka Annisa WCC dalam Penanganan Kekerasan terhadap Perempuan - Kristina Andryani; Felicciana Yayi Amanova; Ikhsan Fauzi A (CV. ITTC INDONESIA, 2026)
The issue of violence against women is rooted in the manifestation of historically unequal power relations between men and women, leading to male domination and discrimination against women. The discourse on violence against women requires ongoing handling through the synergy of various stakeholder elements. Rifka Annisa Women’s Crisis Center is an NGO that is competent in handling issues of violence against women. The services provided by the Rifka Annisa Women's Crisis Center include: handling and assisting victims of gender-based violence, advocating for policies related to women's empowerment, and educating the public to change their mindset towards values and norms that are fair to women by conducting campaigns, training, and research. This study aims to analyze and describe the stakeholders who can influence Rifka Annisa's performance in addressing the discourse of violence against women and the form of implementation of Rifka Annisa WCC's stakeholder communication. This study is a qualitative descriptive study with data collection through documentation studies and in-depth interviews. The data analysis technique uses an interactive analysis model that includes data condensation, data display, conclusion drawing, and verification. The results show that Rifka Annisa WCC prioritizes establishing partnerships with stakeholders in the government and non-government sectors who have the authority and ability to implement programs and policies that can accommodate women victims of violence. Rifka Annisa implements stakeholder communication through hearings, policy advocacy, and training for stakeholders.